Հ.Ի.Լիտինսկու դասարանում (դիտարկումներ «հետխաչատրյանական սերունդ» եզրույթի շուրջ) - Լիլիթ Եփրեմյան (ՀՀ ԳԱԱ հրատ.)
В статье предпринята попытка переоценки творчества так называемого “постхачатуряновского поколения” с точки зрения верности традициям Арама Ильича Хачатуряна. На основе приведенного фактологического материала (писем, отчетов) показано, что в период стажировки в стенах Дома культуры Армении в Москве группа молодых композиторов под руководством Генриха Ильича Литинского была сознательно нацелена на преодоление влияния Хачатуряна. Дух “шестидесятнических” идей пустил ростки в творчестве именно этого поколения, резко сменившего ориентиры на путях раз- вития армянского искусства.In this article an attempt is made to transvalue the works of the so called «post-khachaturian generation» regarding their faithfulness to khachaturyan’s traditions. It is revealed with the help of authentic papers (letters, records) that during traineeships in the Armenian Culture House in Moscow a group of youngcomposers and Henry Litinsky as supervisor had the forethought of overcoming the influence of Aram Khachaturian. The creative spirit of the «sixties» was very prolific. The invaluable compositions of these new generation of composers changed the orientation of the development of Armenian art.
Keywords: Music